The Enemy of My Enemy or About the Uniting Potential of Market Radicalism - Belyavski, Boris (Journal of Economic Sociology, 2020)
This paper is a review of Radical Markets: Uprooting Capitalism and Democracy for a Just Society, the book by Eric A. Posner and Glen E. Weyl and published in 2018. Prof. Posner works at the University of Chicago, where his scholarship is dedicated to international law, foreign relations law, contracts, and game theory and the law. Glen E. Weyl is a Prior Researcher at Microsoft Research New England who also teaches a course Designing the Digital Economy at Yale University. The book concentrates on solutions for the problems of inequality and stagnation. The authors claim that solutions need a combination of left and right theoretical principles. Such a combination allows for institutional systems to approach market principles of freedom, competition, and openness. The market is considered the best tool for providing both equality and economic growth. Five relatively separate spheres are studied in the book, and the same monopolistic restrictions are highlighted. Each chapter presents a solution for one sphere that should enforce free competition and destroy a monopoly. This review proposes an interpretation that the reasonings presented in the book do not create a compromise between left and right. The authors develop a right liberal tradition instead. All the propositions are based on the principles of utilitarianism, marginalist calculations, and neoclassical economics. Simultaneously, the presented solutions appear historically relevant for both approaches, while the solutions do not overcome the theoretical contradictions between neoliberalism and critical theory in the economy and between liberalism and republicanism in politics. The book’s general ideas are discussed after the introduction. Next, specific cases are analyzed through comparison of the principles of liberalism, critical theory, and republicanism. A discussion about the efficiency of theoretical compromises concludes the paper.